If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + 15 = 20 Reorder the terms: 15 + t = 20 Solving 15 + t = 20 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + t = 20 + -15 Combine like terms: 15 + -15 = 0 0 + t = 20 + -15 t = 20 + -15 Combine like terms: 20 + -15 = 5 t = 5 Simplifying t = 5
| =-4x^3+18x | | 1/3n4 | | -2p+1=5 | | (5x+7)-(3x-1)=22 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i+2=0 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i=0 | | 2x^2+5x+3=15 | | 22x^2+5x+3=15 | | 0.5x+2.49=-.07x+6.69 | | 1=b-13 | | 3cos^2x=7sinx+5 | | X-52=100 | | 7x+9y=107 | | 2-3x=-2-2x | | 8-1/4z=1 | | 3,6*4/0,6*8 | | 6v=198 | | 4(x+5)-24=5x-13 | | 13+n=23 | | 25=a/b | | 15=2x+5x+3 | | (10w-9)(8w+7)= | | 2x^4-8x-3=0 | | 4y+5(5-y)-20+2y= | | A=3.1+-09b | | (2y+3)(7y+1)= | | lg(4x-2)=1 | | 10=v+1 | | X(x*x-1)=30 | | 14+x=8x | | 10a+9b=31 | | x(x*x+2x-1)-4x(-2x+3)= |